Hubungan Tingkat Kebersihan Gigi Tiruan Penuh dengan Kejadian Denture Stomatitis - Grant T. H. Mawei; Vonny N. S. Wowor; Christy N. Mintjelungan (e-GiGi, 2023)
Abstract: Dentures can cause new problems for wearers especially individuals who do not under-stand to maintain the cleanliness of the dentures. In case of full denture, mucosal surface covered by the denture can easily be accumulated by plaques inter alia due to Candida albicans which can further cause denture stomatitis. This study aimed to determine the relationship between the level of complete denture hygiene and the incidence of denture stomatitis. This was a literature review study using the Google Scholar, PubMed, and ScienceDirect databases of related topics. The results showed that statistically there was a relationship between denture hygiene and the incidence of denture stomatitis. There was a higher incidence of denture stomatitis in denture users with poor denture hygiene conditions. Poor denture hygiene as a local factor causing denture stomatitis. Numerically, most denture users who experienced denture stomatitis had poor denture hygiene. In conclusion, statistical and numerical tests showed that there is a relationship between the level of denture hygiene and denture stomatitis in full denture users. Keywords: denture hygiene level; complete denture wearers; denture stomatitis Abstrak: Pemakaian gigi tiruan dapat menimbulkan masalah bagi penggunanya terlebih pada individu yang kurang memahami pemeliharaan kebersihan gigi tiruan. Pada penggunaan gigi tiruan penuh, pada permukaan mukosa yang tertutup gigi tiruan dapat dengan mudah terjadi akumulasi plak antara lain oleh Candida Albicans yang dapat menyebabkan terjadinya denture stomatitis. Penelitian ini bertujuan untuk mengetahui hubungan tingkat kebersihan gigi tiruan penuh dengan kejadian denture stomatitis. Jenis penelitian ialah suatu literature review yang menggunakan database Google Scholar, PubMed, dan ScienceDirect dengan topik yang terkait. Hasil uji statistik pada literatur yang digunakan mendapatkan adanya hubungan/pengaruh antara kebersihan gigi tiruan dengan kejadian denture stomatitis. Kejadian denture stomatitis lebih tinggi pada pengguna gigi tiruan dengan kondisi kebersihan gigi tiruan yang buruk. Kebersihan gigi tiruan yang buruk sebagai faktor lokal penyebab denture stomatitis. Secara numerik pada pengguna gigi tiruan yang mengalami denture stomatitis, sebagian besar memiliki kebersihan gigi tiruan yang buruk. Simpulan penelitian ini ialah uji statistik dan numerik memperlihatkan adanya hubungan antara tingkat kebersihan gigi tiruan dengan denture stomatitis pada pengguna gigi tiruan penuh. Kata kunci: tingkat kebersihan gigi tiruan; pengguna gigi tiruan penuh; denture stomatitis